Ameliorative effect of Amaranthus tricolor L. leaves on scopolamine-induced cognitive dysfunction and oxidative stress in rats - Vrushabh B. Hupparage, Vijaykumar P. Rasal, Vishal S. Patil&, Priyanka P. Patil&, Shubham G. Mulange, Ajay P. Malgi, Sathgowda A. Patil, Ashwini R. Karade (Journal of Applied Pharmaceutical Science, 2020)
Ayurveda is a holistic system that uses mostly herbs and minerals in prescriptions that play a crucial role in the treatment of various diseases because of their therapeutic effects, often on multiple targets. In the present study, we assessed the memory-enhancing activity of a leafy vegetable “Amaranthus tricolor L.” against scopolamine (SCP)- induced cognitive dysfunction and oxidative stress in rats. Initially, we screened A. tricolor leaves’ ethanolic extract for its acetylcholinesterase (AChE) inhibitory and antioxidant activity using standard procedures. The memory-enhancing activity in rats was performed by using the Morris water maze (MWM), the elevated plus maze (EPM), Actophotometer, and Cook’s pole climbing (CPC) apparatus. Biochemical parameters, mainly AChE and butyrylcholinesterase (BChE) enzyme levels measured in the hippocampus and cortex, amyloid beta, reduced glutathione (GSH), superoxide dismutase, and lipid peroxidation (LPO) level, were measured in whole brain tissue. A. tricolor leaves’ extract showed potent AChE inhibition and antioxidant activity on the scavenging of 2,2-diphenyl-1-picryl-hydrazyl-hydrate (DPPH). The EPM, MWM, CPC, and Actophotometer showed that SCP administration increased transfer latency (TL) and decreased escape latency time (ELT) and locomotion, respectively, on day 7 and 14, whereas combined therapy of SCP with Donepezil and SCP with 800 mg/kg A. tricolor extract significantly reversed the ELT, TL, and locomotion from day 7 to 14. Moreover, AChE and BChE activities and GSH and Malondialdehyde (MDA) levels were significantly elevated in SCP-treated rats, and treatment with A. tricolor elevated the biochemical parameters altered by the SCP administration. A. tricolor L. leaves’ extract ameliorates SCP-induced cognitive dysfunction and oxidative stress by the restoration of the cholinergic system’s function, inhibiting Amyloid precursor protein (APP) deposition, and via antioxidant potency, i.e. increasing GSH level, by inhibiting the LPO in the brain. The current study suggests that A. tricolor L. leaves could be a valuable source for the treatment of cognitive dysfunction and oxidative stress associated with Alzheimer’s disease.
Keywords: Cognitive dysfunction, Alzheimer’s disease, Amaranthus tricolor L., Scopolamine, Donepezil, Neuroprotective.